1999
DOI: 10.1111/j.1553-2712.1999.tb01207.x
|View full text |Cite
|
Sign up to set email alerts
|

History of Domestic Violence among Male Patients Presenting to an Urban Emergency Department

Abstract: Abstract. Objective: To establish the prevalence of domestic violence committed by women against male patients presenting to an urban ED for any reason. Methods: This was a prospective survey in which male patients of legal age presenting to the ED over a 13-week period were interviewed. Patients answered a series of six questions adapted from the George Washington University Universal Violence Prevention Screening Protocol. Patients who could not speak English, those refusing to participate, those unable to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 20 publications
1
44
1
5
Order By: Relevance
“…41,42 Several studies have reported that men screened in the ED for IPV had similar rates of victimization by an intimate partner as women. 43,44 These studies and our own screening results might be documenting a high rate of low-level, bidirectional emotional or physical violence 45 and do not make a clear distinction between a victim or a perpetrator. One trauma unit study linked the names of men presenting to an ED with injuries inflicted by their female partner to police department records and found that half of these men had prior arrests for domestic violence perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Several studies have reported that men screened in the ED for IPV had similar rates of victimization by an intimate partner as women. 43,44 These studies and our own screening results might be documenting a high rate of low-level, bidirectional emotional or physical violence 45 and do not make a clear distinction between a victim or a perpetrator. One trauma unit study linked the names of men presenting to an ED with injuries inflicted by their female partner to police department records and found that half of these men had prior arrests for domestic violence perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar das severas consequências decorrentes da violência praticada por parceiro íntimo em ambos os sexos, a maioria das pesquisas que investigam a violência por parceiro íntimo é voltada às mulheres como vítimas e aos homens como agressores 11,12 , e é majoritariamente realizada em países desenvolvidos 7,13,14,15,16,17 . Portanto, há escassez de estudos que contemplem a violência por parceiro íntimo em homens 11 .…”
Section: Introductionunclassified
“…[20][21][22][23][24][25] Health-care research on IPV and men, though, is quite limited. There are few studies that explore its prevalence in the health-care setting, [26][27][28][29][30] the accuracy and efficacy of medical screening, 29,31,32 the ability of interview procedures to distinguish victimization from perpetration, 32,33 and the efficacy of a health-care responses to men, including of batterer's treatment programs. 34,35 Although published expert experience exists, 33,[36][37][38][39][40][41][42] there are no comprehensive healthcare guidelines on addressing IPV specifically with men.…”
Section: Introductionmentioning
confidence: 99%